Resource nationalism in Southern Africa : ethnic control and political ideology - Berry, Neil Alexander (Department of Political Studies, 2015)
In the West nationalisation and privatisation have been explained mostly in relation to the political ideologies of capitalism and socialism. The privatisations that began in the 1980s, and accelerated after the collapse of socialism across Eastern Europe, have generally been considered to be developmentally linear. Postcolonial nationalisation-privatisation cycles in South East Asian and Latin American countries, by contrast, have been explained by scholars such as Chua as related to ethnicism, nationalism and indigenism and above all the presence of a 'emarket dominant ethnic minority f (MDM). This paper reviews the cycles of nationalisation and privatisation in the mining industries in Zambia and South Africa (SA), in order to examine the respective roles that ethnicity and political ideology have played. It explores whether minority ethnic economic control is more important than political ideology in driving calls for nationalisation of mining. For each country case, I set out a detailed historical analysis of the political and policy provisions made since independence from colonial rule. The paper explores ideas of ownership and race; the internalisation of norms of neoliberal economic policies; socialism and nationalism; and power relations and identity politics. The study also interrogates the impact of global structures upon state decisions. In both case studies, I show that minority ethnic dominance has been a more important driver of nationalisation/privatisation cycles than political ideology.